UMPSA to open Kuala Lumpur Learning Centre as part of its vision to become an Advanced TVET Hub in ASEAN - Mimi Rabita, Abd Wahit (UMPSA, 2025)
KUALA LUMPUR, 1 August 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is set to establish the UMPSA Kuala Lumpur Learning Centre (UMPSA KL) as part of its mission to expand access to higher education—particularly Technical and Vocational Education and Training (TVET)—for urban communities and working professionals.